PERANAN ALAT BUKTI DALAM PERKARA PIDANA DALAM PUTUSAN HAKIM MENURUT KUHAP - Bastianto Nugroho (Yuridika, 2017)
The trial of a criminal case is to find out whether a criminal offense has occurred in an event, therefore in the most important criminal proceedings the proceedings are proved. Evidence is a problem that plays a role in the examination process in court because with this proof is determined the fate of a defendant. The legal function in the State of Indonesia is to regulate the order of society in the life of the nation and the state, whereas the violation of the law itself is an event that must exist in every society and is impossible to be eliminated absolutely, because violation of law is an integral part of development More complex. One of the provisions governing how the law enforcement officers carry out the task in the field of repressive is the criminal procedure law which has the purpose of searching and approaching material truth, the complete truth of a criminal case by applying the provisions of criminal procedure law honestly darn precisely with The purpose of finding out who the perpetrator can be charged with is a violation of the law.